Reversing stage III oral adenocarcinoma in a dog treated with anti-canine PD-1 therapeutic antibody: a case report - Xu, Shuo; Xie, Jingshu; Wang, Shuaiyu; Tang, Na; Feng, Junli; Su, Youhong; Li, Gebin (Frontiers in Veterinary Science, 2023)
Monoclonal antibody targeting programmed cell death-1 (PD-1) is one of the most promising treatment therapies for human cancers. Canine PD-1 antibodies used in clinical trials have also shown efficacy in treating canine cancers. An 11-year-old male intact border collie presented to us for evaluation of left cervical mass. Computed tomography (CT) examination revealed an irregular pharyngeal mass invading the surrounding soft tissue. Histological and immunohistochemical results were consistent with a diagnosis of adenocarcinoma, most likely originating from the minor salivary gland. An anti-canine PD-1 monoclonal antibody was administered. Two months after the initial treatment, the tumor reached partial remission and maintained as such for six months. Finally, the patient was euthanized due to reasons unrelated to cancer, with a survival time of 316 days. To our knowledge, this is the first report of response to PD-1 blockade treatment in canine adenocarcinoma.